1998
DOI: 10.1104/pp.117.4.1487
|View full text |Cite
|
Sign up to set email alerts
|

Rate-Limiting Steps in Selenium Assimilation and Volatilization by Indian Mustard1

Abstract: Se can be accumulated by plants and volatilized to dimethylselenide, providing an attractive technology for Se phytoremediation. To determine the rate-limiting steps in Se volatilization from selenate and selenite, time-and concentration-dependent kinetics of Se accumulation and volatilization were studied in Indian mustard (Brassica juncea). Time-dependent kinetic studies showed that selenate was taken up 2-fold faster than selenite. Selenate was rapidly translocated to the shoot, away from the root, the site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
155
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(182 citation statements)
references
References 25 publications
25
155
2
Order By: Relevance
“…However, this statement was during our experiments with S. alba fully confirmed for selenite, discrepancy was observed for selenate when transformation index (Ti) for tested concentrations did not exceed value 0.39 (Table 3). Results for selenate are in agreement with those of de Souza et al (1998). These authors determined through Se timedepending kinetic that only 10% of selenates absorbed by Indian mustard (Brassica juncea) moved from the roots into the shoots.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, this statement was during our experiments with S. alba fully confirmed for selenite, discrepancy was observed for selenate when transformation index (Ti) for tested concentrations did not exceed value 0.39 (Table 3). Results for selenate are in agreement with those of de Souza et al (1998). These authors determined through Se timedepending kinetic that only 10% of selenates absorbed by Indian mustard (Brassica juncea) moved from the roots into the shoots.…”
Section: Discussionsupporting
confidence: 80%
“…Selenium lower toxicity in seedlings shoots can be explained by transformation of inorganic selenium to organic compounds that are transported from the roots to the shoots , Kahakachchi et al 2004). Many authors (de Souza et al 1998, Kahakachchi et al 2004, Zayed et al 1998 www.plantroot.org 18 2009) introduced very weak selenite translocation from the roots to the shoots and this statement also confirmed here introduced results (Table 3). By this low translocation and Se storage in the roots can also explain many times higher IC 50 values for shoots than those for roots growth reduction.…”
Section: Discussionsupporting
confidence: 77%
“…Approximately 10 times more DMeSe and DMeDSe (normalized to sample weight) is produced in all plant types when the plants were supplemented with selenite than with selenate (8).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the absorption of selenite occurs in a different way (Terry et al, 2000), through a phosphate transporter (Zhao et al, 2010). Once absorbed, selenite remains in organic form (De Souza et al, 1998;Cartes et al, 2006) and has been shown to be a more efficient inducer of glutathione peroxidase (Cartes et al, 2005). Selenium is thought to be associated with antioxidant metabolism (Lin et al, 2012;Feng et al, 2013) through its function as a cofactor of selenoenzymes (Combs, 2001); its deficiency could provoke changes in the cellular redox balance.…”
Section: Introductionmentioning
confidence: 99%
“…Selenate is absorbed through a transport process coupled to a H + -ATPase, with the help of a sulfate (Terry et al, 2000) or silicon transporter (Zhao et al, 2010); once absorbed by the plants, maintains the inorganic form (De Souza et al, 1998;Cartes et al, 2006). In contrast, the absorption of selenite occurs in a different way (Terry et al, 2000), through a phosphate transporter (Zhao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%